SURFACE DISPLACEMENT MEASUREMENT FROM REMOTE SENSING IMAGES - CAVALIE, OLIVIER (JOHN WILEY, 2022)
Drastic improvements in both access to satellite images and data processing tools today allow near real-time observation of Earth surface deformations. Remote sensing imagery is thus a powerful, reliable and spatially dense source of information that can be used to understand the Earth and its surface manifestations as well as mitigate natural hazards. This book offers for the first time a complete overview of the methodological approaches developed to measure surface displacement using synthetic aperture radar (SAR) and optical imagery, as well as their applications in the monitoring of major geophysical phenomena. More specifically, the first part of the book presents the theory behind SAR interferometry (InSAR) and image correlation and its latest developments. In the second part, most of the geophysical phenomena that trigger Earth surface deformations are reviewed. Surface Displacement Measurement from Remote Sensing Images unveils the potential and sensitivity of the measurement of Earth surface displacements from remote sensing imagery.